Anion Exchange in Lead Halide Perovskites: An Overview. Issue 4 (21st January 2022) - Sandeep, K.; Padmakumar, K.; Ambili, K. U.; Jishnu, P.; Fousia, K. H.; Ramesh, A. R.; Rappai, John P.; Santhi, V.; Shanthil, M.
Abstract : Precise tuning of the bandgap of lead halide perovskites by the postsynthetic anion exchange reaction has been considered as one of the best methods to customize their optical/electronic properties. The anion exchange reaction of lead halide perovskites is very fast and occurs at room temperature. The crystal structure of the lead halide perovskites is soft, and hence it facilitates diffusion of the halide ions through the crystal lattice. Through this anion exchange reaction, emission of lead halide perovskites can be tuned in the entire visible range, by varying the amounts of chloride, bromide, and iodide ions from the same synthesis in a cost‐effective manner. Herein, the mechanism involved in the anion exchange reactions and the factors influencing the same are discussed. Also, the discussion is extended to demonstrate how anion exchange process can make lead halide perovskite a more promising candidate for various applications. Abstract : Anion exchange reactions in lead halide perovskites by postsynthetic methods can tune the property of these materials for a wide range of applications. The soft crystal nature facilitates the motion of anions through the crystals lattice, allowing for the exchange of halide ions. Herein, the mechanism and applications of these materials in light‐emitting devices, sensors, photovoltaics, and photocatalysts are described.